Homogeneous Besov spaces associated with the spherical mean operator - Rachdi, L.T.; Rouz, A. (CUBO, A Mathematical Journal, 2011)
We define and study homogeneous Besov spaces associated with the spherical mean operator. We establish some results of completeness, continuous embeddings and density of subspaces. Next, we define a discrete equivalent norm on this space and we give other properties.